Development of an Automated Training Device for Macaque Monkeys - Noroozi, Jalaledin; Ahmadi, Mahsa; Shahamati, Atlas; Rezayat, Ehsan; Dehaqani, Mohammad-Reza A. (Basic and clinical neuroscience, 2025)
Introduction: Training macaques for cognitive and behavioral tasks is often time-consuming, stressful, and requires extensive human involvement. Traditional chair-based methods may take weeks or months and can negatively affect animal welfare. To address these challenges, we developed an automated, cage-based training device. Methods: Two adult male rhesus macaques were trained using the device step-by-step on working memory, delayed match-to-sample, starting from simple screen touches and progressing to the full task. Results: The monkeys interacted well with the device, and the system reduced stress by eliminating the need for chair restraint. Training time was shortened, and both monkeys successfully learned the task within 30–33 days. Conclusion: This automated training device provides an efficient, cost-effective, and welfare-friendly alternative to conventional training methods for monkeys. It shortens training duration, improves task acquisition, and enhances enrichment, offering a promising tool for neuroscience research with non-human primates.